Parental Posttraumatic Stress Disorder and Attunement: Meta-Analysis - Asanov, Julia; Rehman, Neelofar (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: Attunement between a primary carer and their infant plays a crucial role in infant brain development, attachment, sense of self and personality development, with long-term effects on risk of future psychopathology. The present study aimed at 1) identifying a comprehensive definition of attunement and 2) investigating parent-infant attunement in the context of parental posttraumatic stress disorder (PTSD). Subjects and Method: Following PRISMA guidelines, a systematic review of the literature was conducted on parental PTSD and parent-infant attunement. Eligible studies were prospective, quantitative, published in peer-reviewed journals, included normal samples and samples with PTSD along with attunement variables, reporting correlational data, with mothers aged 16 or older and infants aged 0-18 months. 48 articles were examined in full-text and 18 selected for analysis. A National Heart, Lung, and Blood Institute (NHLBI) quality assessment tool was used to assess the quality of selected studies. Pooled effect sizes were calculated separately for positive and negative attunement variables under the random effects model, using comprehensive meta analysis (CMA). Results: Analysis failed to reach statistical significance. The pooled effect size for parental PTSD and negative attunement was positive and small. The pooled effect size for parental PTSD and positive attunement was negative and small. Conclusion: Due to the high heterogeneity among the included articles and statistically non-significant effect sizes, results need to be interpreted with caution. However, the results indicate that the presence of PTSD symptoms is likely to influence parents’ capacity to attune to their infants. Limitations and implications for future research and clinical practice are discussed.